Model Project Citizen untuk Meningkatkan Kemampuan Berpikir Kritis dalam Mengatasi Dampak Media Sosial (Prosiding Konseling Kearifan Nusantara (KKN), 2025)
ABSTRACTThe use of social media among adolescents has become increasingly widespread, even leading to addiction, which results in negative impacts both physically and psychologically. These negative effects can influence four areas of guidance and counseling services: personal, academic, social, and career aspects, thus threatening the achievement of developmental tasks. In addition to being responsible for themselves, students are also part of a nation and, more locally, a student group at their school. As members of this community, students need to think critically about how they can play an active role in ensuring that those around them are protected from the negative effects of social media. Therefore, effective and engaging guidance and counseling strategies are needed to help students face these impacts. This article proposes the application of Project Citizen as an approach that can enhance student engagement in classical services, identify the negative impacts of social media, think critically to take a stance, and develop school policies that can protect students from the negative effects of social media.